Memory assessment software in a dementia clinic: a pilot study using improvement science. - Leroi, Iracema; Hendry, Ann Marie; Critcher, Sandra; Chavunduka, Barbara; Allen, Tom (British Journal of Neuroscience Nursing)
Background: The pressure on memory assessment services in the UK to undertake an increasing number of new patient assessments is growing. Digital assessment tools delivered on hand-held electronic devices, such as tablets, may optimise the efficiency, accuracy and usefulness of remote cognitive assessments. Aim: To pilot the introduction of cognitive assessment software delivered on tablets in domiciliary-based memory assessments. Methods: Using the principles of improvement science (IS), the authors undertook a 12-month prospective technology introduction study, using a change package with an interrupted time series design. New tablet-based auto-scoring assessment software was systematically introduced in one mental health Trust in the North West UK to improve the efficiency of the assessment and report preparation process. Changes involved incrementally adapting the software with assessment nurses in a series of ‘Plan Do Study Act' (PDSA) cycles evaluated with time series run charts. Results: Application of the final version of the software reduced the mean time taken to score and prepare the clinical assessment report by nearly 84% from the baseline (a median improvement of 77.5 minutes). This equates to a substantial increase in the number of new assessments that could be undertaken per year due to increased availability of front-line care. Conclusion: Introducing tablet-compatible assessment software for homebased memory clinics significantly increases the efficiency of the process and may facilitate more rapid turnover of new patient referrals. IS methods have potential to aid the introduction of new technology to improve dementia care.